ISRAEL: FINDING THE LEVANT WITHIN THE MEDITERRANEAN - Harris, Rachel S. (The Levantine Review, 2012)
Reviews of: Alexandra Nocke. The Place of the Mediterranean in Modern Israeli Identity. Brill 2010, Cloth 70. ISBN 9789004173248 Amy Horowitz. Mediterranean Israeli Music and the Politics of the Aesthetic. Detroit: Wayne State University Press, 2010. Paper 29.95. ISBN 9780814334652. Karen Grumberg. Place and Ideology in Contemporary Hebrew Literature. Syracuse: Syracuse University Press, 2011. Cloth 39.95. ISBN 9780815632597.